Sanitation in unsewered urban poor areas: technology selection, quantitative microbial risk assessment and grey water treatment - Katukiza, Alex Y. (Wageningen University and Research, 2013)
The sanitation crisis in unsewered urban slums of cities in developing countries is one of the challenges that need to be addressed. It is caused by the high rate of urbanisation in developing countries and the increasing urban population with limited urban infrastructure. The major issues of concern are the collection, treatment and safe disposal of excreta, grey water and solid waste. The goal of this study was to contribute to the sanitation improvement in urban slums with focus on sanitation technologies. A review of sanitation technology options for urban slums was made followed by a baseline study in the slum of Bwaise III in Kampala Uganda. The results from the situation assessment and analysis were used to develop a method for selection of sustainable sanitation technologies in urban slums. Quantitative microbial risk assessment was then carried out based on the sources and concentration of pathogens and indicator organisms in the slum environment. The risk of infection and the disease burden contribution from various exposure pathways were determined. The study then focused on grey water treatment using a low-cost media (sand, crushed lava rock) based systems at laboratory scale and household level in the study area.
Keywords: sanitation; sanitation crisis; water treatment